(3GdeLehYI GdCOHjIs - (3eLehYI ef GdeDdajfs ((3GdbSWfWjfjI s)
(3ChdgG (B:s
(3ai GdUMGM ai X d a Xda faSg Yf GdTF jXdagG Ci UfYgG ef Cf JaYdg Ch JCJjg bGd GdTGYQ dbO CXda GdfaS Yf eWYe s
(3BNQgG (B:s
(3hEfi dUhGf dfaSi hGffi Ydi Gdghd CMjGfkG HgG GdQMhe hEfi dCRQi ai NdGd cKjQI Ydi GdeQA Cf jNJGd hgh dFje s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs